Using Participatory Design to Inform the Connected and Open Research Ethics (CORE) Commons. - Harlow, John; Weibel, Nadir; Al Kotob, Rasheed; Chan, Vincent; Bloss, Cinnamon; Linares-Orozco, Rubi; Takemoto, Michelle; Nebeker, Camille (Science & Engineering Ethics, 2020)
Mobile health (mHealth) research involving pervasive sensors, mobile apps and other novel data collection tools and methods present new ethical, legal, and social challenges specific to informed consent, data management and bystander rights. To address these challenges, a participatory design approach was deployed whereby stakeholders contributed to the development of a web-based commons to support the mHealth research community including researchers and ethics board members. The CORE (Connected and Open Research Ethics) platform now features a community forum, a resource library and a network of nearly 600 global members. The utility of the participatory design process was evaluated by analyzing activities carried out over an 8-month design phase consisting of 86 distinct events including iterative design deliberations and social media engagement. This article describes how participatory design yielded 55 new features directly mapped to community needs and discusses relationships to user engagement as demonstrated by a steady increase in CORE member activity and followers on Twitter.